Kualitas Aparatur, Sistem Informasi, Sistem Pengendalian Intern, dan Efektivitas Manajemen Aset Tetap - Astini, Yuli (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 13 No 2 (2018)DO - 10.24843/JIAB.2018.v13.i02.p10, 2018)
The purpose of this study is to prove empirical ly about the effect ofi nformation systems and internal control systems on the effectiveness of fixed asset management with the quality of apparatus as a moderating variable . This research conducted at Badan Pengelolaan Keuangan dan Aset Daerah (BPKAD)West Lombok, Central Lombok, East Lombok and North Lombok . The number of samples in this study were 64 respondents, with sampling using purposive sampling method . The data collected by questionnaires and data analysis techniques using moderated regression analysis (MRA). The results of this study prove s empirical ly that information system has a negative and significant effect on the effectiveness of fixed asset management, internal control system has a positive and significant effect on the effectiveness of fixed asset management, and the quality of the apparatus moderate the effect of information systems and internal control systems on the effectiveness of fixed asset management. Keywords: Quality apparatus , information system , internal control syste ,  fixed asset management effectiveness.